Out of the Shadows : the Life and Works of Mary De Morgan. - Pemberton, Marilyn (Cambridge Scholars Pub., 2012)
Who was Mary De Morgan and why should she be dragged out of the shadows cast by her illustrious parents, her male siblings and the members of the Arts and Crafts circle in which she moved? Why should the academic spotlight be shone onto her life and works? De Morgan (1850-1907) was undoubtedly a woman of her time: she was unmarried and therefore one of the million or so "odd" women who had to earn their own living, which she did mainly by writing. She was one of the many who took part in the ...